Legal Power Of Binding Sale And Purchase Agreements (PPJB) In The Transfer Of Rights To Land And Buildings - Yuliyanti, Renny; Dewi Navisa, Fitria; Sunardi, Sunardi (International Significance of Notary, 2025)
Abstract : Preliminary Sale and Purchase Agreement or Sale and Purchase Agreement (hereinafter referred to as PPJB) of land and buildings under the control of a Notary is also a form of legal and binding agreement for the parties who make it, as long as there is no denial of the agreement. , this is in accordance with Article 1338 Civil Code, however in the dispute over the decision of the Malang District Court Number 27/PDT.G/2020/PN.MLG. The judge did not rule on breach of contract against the developer CV. Dua Sekawan who did not carry out some of the achievements in the PPJB, namely not continuing the process to AJB and changing the name of the certificate for the plot of land and building they sold; Meanwhile, the plaintiff/buyer Mrs. Siti Maryam, has paid the installments for the purchase of the house as required in the PPJB they made.The problem formulation is 1) What is the legal force of PPJB in the process of transferring rights to plots of land and buildings? 2) What is the view of SEMA No. 4 of 2016 concerning the Implementation of the Formulation of the Results of the 2016 Supreme Court Chamber Plenary Meeting as Guidelines for the Implementation of Duties for the Court regarding land rights transfer transactions with PPJB?. This type of research is classified as normative research which focuses on case studies and facts that occurred based on the decision of the Malang District Court Number 27/PDT.G/2020/PN.MLG. accompanied by a review of the literature. This research is descriptive in nature which aims to describe clear and systematic details of the main problem.The results of the research are that PPJB is included in the scope of contract law, so the position of PPJB is valid and binding on the parties who make it in accordance with Article 1320 of the Civil Code, conversely if it does not fulfill the conditions for the validity of the agreement then the PPJB will give rise to legal consequences, namely that it can be canceled and/or null and void by law. Based on the Civil Code regarding contracts, it should be enough for the judge to decide on the developer's breach of contract CV. Dua Sekawan. Regarding the transition of HAT to PPJB, Supreme Court Circular No. 4 of 2016 as a guideline for implementing duties for courts and judges has also specifically emphasized that the transfer of land rights based on a Sale and Purchase Agreement (PPJB) legally occurs if the buyer has paid the price of the land in full and has controlled the object of sale and purchase and is done in good faith. . So judges should be able to dig deeper and make legal discoveries using doctrine, regulations and jurisprudence so that they can provide legal certainty and a sense of justice to plaintiffs/buyers.